The Interferon Response Dampens the Usutu Virus Infection-Associated Increase in Glycolysis - Wald, Maria Elisabeth; Sieg, Michael; Schilling, Erik; Binder, Marco; Vahlenkamp, Thomas Wilhelm; Claus, Claudia (Frontiers in Cellular and Infection Microbiology, 2022)
The mosquito-borne Usutu virus (USUV) is a zoonotic flavivirus and an emerging pathogen. So far therapeutical options or vaccines are not available in human and veterinary medicine. The bioenergetic profile based on extracellular flux analysis revealed an USUV infection-associated increase in glycolysis on Vero and to a lesser extent on an avian cell line derived from Eurasian blackbirds. Glycolysis contributed to production of virus progeny, as inhibition of glycolysis with 2-deoxy-D-glucose reduced virus yield on Vero by one log step. Additionally, the increase in glycolysis was lost after the addition of exogenous type I interferon (IFN) β to USUV-infected Vero cells. To further explore the contribution of the IFN response pathway to the impact of USUV on cellular metabolism, USUV infection was characterised on human A549 respiratory cells with a knockout of the type I IFN receptor, either solely or together with the receptor of type III IFN. Notably, only the double knockout increased permissiveness to USUV followed by an alteration of the glycolytic activity. This study provides evidence for glycolysis as a possible target for therapeutic intervention of USUV replication. Moreover, presented data highlight type I and type III IFN system as a determinant for human host cell permissiveness and for the infection-associated impact on glycolysis.